The effect of tropical weathering on durability properties of sandstone and shale at Iskandar Puteri - 614218 Al Mujida Ali Musa, 1995- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018